Seismic performance test research on a new type of replaceable energy-consuming joint column. Issue 166 (March 2023) - Ye, Yanxia; Wang, Zongbin; Yang, Zhihao; Hou, Zhiyuan; Qiao, Pengshuang
Abstract: This study proposed a new type of fully-precast reinforced concrete column-column joint, a replaceable energy-consuming joint (RECJ), which was composed of tenons and replaceable energy-dissipating connecting plates. The joint's seismic behavior and failure mechanism were investigated using quasi-static tests on two RECJ-connecting precast columns, one cast- in situ column, and one repaired RECJ-connecting precast column. The results showed that the damage and destruction of RECJ-connecting specimens were mainly concentrated on the connecting steel plates, while the other parts were basically elastic, showing a compression-bending failure mode. The hysteresis curves of RECJ-connecting specimens were fully shuttle-shaped. Meanwhile, energy dissipation, ductility, and stiffness degradation performance of these specimens were significantly better than those of the monolithic concrete comparison column. At the same time, the specimen with a longer tenon exhibited better overall seismic performance than that with a shorter tenon, while having the same initial stiffness and bearing capacity as the cast- in situ column. The seismic performance of the repaired long-tenon RECJ-connecting specimen with connecting plates replaced was not significantly decreased compared with original specimen, which demonstrated that RECJ had fine repairability. The relevant parameters were optimized through finite element simulation (FEM). Finally, based on test results, the shear capacity equation of RECJ was deduced according to the force equilibrium of an isolated body in the joint area and the accuracy of the equation verified. Highlights: This study proposed a new type of fully-precast reinforced concrete column-column joint(RECJ), a replaceable energy-consuming joint. The seismic performance of the repaired specimen was not significantly decreased compared with original specimen. These parameters were optimized through FEM, and the reasonable value range of relevant parameters was obtained. The shear capacity equation of RECJ was deduced in the joint.